2021
DOI: 10.2989/10220119.2020.1838608
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil surface scarification and reseeding with sulla (Hedysarum coronarium L.) of degraded Mediterranean semi-arid rangelands

Abstract: Climate change and degradation of natural resources pose daunting challenges in arid and semi-arid rangelands of southern Mediterranean region. Overcoming these challenges requires considerable management actions efforts. In this context, the current two-year (2017/2018 and 2018/2019) study investigated the effects of soil surface scarification and reseeding of rangelands with sulla (Hedysarum coronarium L.) on botanical composition, biomass production, water productivity and pastoral value in the Sbaihia comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Using native drought-tolerant forage species for enhanced dryland pasture restoration (Blog) by Mounir Louaichi (2021). Assessment of soil surface scarification and reseeding with sulla (Hedysarum coronarium L.) of degraded Mediterranean semiarid rangelands (Slim et al, 2021). Managing rangelands: promoting sustainable legume species: Hedysarum coronarium L.: a biennial herbaceous legume used for forage in the Mediterranean basin (Louhaichi, Slim and Gouider, 2018).…”
Section: Management Practices Resulted In Several Social and Environm...mentioning
confidence: 99%
“…Using native drought-tolerant forage species for enhanced dryland pasture restoration (Blog) by Mounir Louaichi (2021). Assessment of soil surface scarification and reseeding with sulla (Hedysarum coronarium L.) of degraded Mediterranean semiarid rangelands (Slim et al, 2021). Managing rangelands: promoting sustainable legume species: Hedysarum coronarium L.: a biennial herbaceous legume used for forage in the Mediterranean basin (Louhaichi, Slim and Gouider, 2018).…”
Section: Management Practices Resulted In Several Social and Environm...mentioning
confidence: 99%
“…With the aid of a ruler, the length (l) and width (w) of individual leaves were measured. Approximate individual leaf area was calculated as Individual leaf area = l × w cm 2 The area of individual leaves per plant was summed up to obtain approximate total plant leaf area. At harvest, shoot fresh biomass was determined on the whole harvested plant.…”
Section: Shoot Biometrymentioning
confidence: 99%
“…Suitable for harsh environments, it is a key forage in northern Africa (Morocco, Algeria, Tunisia), Egypt, Turkey, and Lebanon [1]. Research in Tunisia has shown how reseeding sulla into degraded semi-arid rangelands improves forage yield, land pastoral value, and water productivity [2] and considerably reduces overland flow and soil erosion compared to fallow or wheat [3].…”
Section: Introductionmentioning
confidence: 99%